Authentic Leadership Kepala Sekolah dalam Menanamkan Sistem Nilai - Aan Komariah (Universitas Negeri Malang, 2013)
Abstract: The Authentic Leadership of School Principals in Inculcating Value System. The present article reports on a research project aimed at examining the extent to which " authentic ladership" is important as an alternative leadership model to apply at schools to inculcate value and character systems of the school community. It was also aimed at examining the dimensionality of the authentic leaderhip . Delphi Survey method was implemented to assess the importance of authentic leadership. The study involved 62 superintendants who were formerly principals of secondary schools, high schools, and vocational schools in Bandung, West Java. The results show that authentic leadership was a suitable type of leadership model to effectively instill value system. It also demonstrated that authentic leadership was a unidimensional construct. Abstrak: Authentic Leadership Kepala Sekolah dalam Menanamkan Sistem Nilai. Penelitian ini bertujuan untuk menguji seberapa penting authentic leadership untuk dijadikan sebagai alternatif kepemimpinan di sekolah untuk menanamkan sistem nilai dan karakter warga sekolah serta menguji multidimensionalitas konstruk authentic leadership di sekolah. Metode Delphi Survey digunakan untuk pengujian tingkat pentingnya perilaku authentic leadership dengan partisipan 62 pengawas mantan kepala sekolah SMP, SMA dan SMK di Kota Bandung. Hasil penelitian menunjukan bahwa authentic leadership adalah tipe kepemimpinan yang tepat untuk menanamkan sistem nilai secara efektif. Penelitian juga membuktikan bahwa authentic leadership merupakan konstruk yang bersifat unidimensional.